Shrek 2 [videorecording (Blu-Ray)] - Adamson, Andrew; Steig, William, 1907-2003 (Universal Pictures Home Entertainment, 2018)
Shrek and Princess Fiona are going to meet her parents, who are in for a surprise when they see how much their daughter has changed and that she has married the ogre Shrek. Her father the King now must enlist help to make his dreams come true. Special features include commentary, and featurettes.